Biological anolyte regeneration system for redox flow batteries. Issue 15 (2nd February 2023) - Simoska, Olja; Rhodes, Zayn; Carroll, Emily; Petrosky, Katia N.; Minteer, Shelley D.
Abstract : A microbial-based system for redox flow battery (RBF) electrolyte regeneration system to address failure mechanisms in RBF devices. Abstract : Redox flow battery (RFB) electrolyte degradation is a common failure mechanism in RFBs. We report an RFB using genetically engineered, phenazine-producing Escherichia coli to serve as an anolyte regeneration system capable of repairing the degraded/decomposed redox-active phenazines. This work represents a new strategy for improving the stability of RFB systems because, under the influence of genetically engineered microbes, the anolyte species does not display degradation after battery cycling.